O conhecimento matemático na educação infantil: o movimento de um grupo de professoras em processo de formação continuada - Azevedo, Priscila Domingues de (2012)
This research investigated what are the mathematical and methodological knowledge produced, recognized and redefined by teachers of childhood education, when they gather in a study group about mathematics education in childhood; and what are the signs of professional development manifested by the participants of the group in the process of continuing training. The objectives were: to analyse the formative processes of constitution and maintenance of the GEOOM group; to highlight the learning process that started from within the group; and identify the production, recognition and ressignification of the mathematical and methodological knowledge revealed in the oral and written narratives. This is a survey of qualitative nature that, through the analysis of content, followed the process of setting up and maintaining a group in which 39 childhood education teachers of the municipal network of São Carlos/SP met and lived - in moments and spaces of time not always coincident - for five semesters. The empirical materials were built from the reflexive narratives (oral and written) produced by the teachers, the reflective journal from the trainer-researcher and questionnaires (initial and final) answered by the teachers. From the data, the following aspects were identified: the conceptions of child education and mathematical education of teachers participant in the group; methodological approaches resized by the teachers in the process of formation in the group; the mathematical knowledge that are workable from games, children's stories and situations problems; the aspects of collaborative learning that occurred in the group; and the group blog as a means of socialization of the knowledge produced. The theoretical framework was sustained by the studies of Barbosa and Faria, Kishimoto and Grando, Van de Walle and Moura, Imbernón, Hargreaves, Ponte, Day, Fiorentini, among others. The mutual help between the involved and the relationship of trust established in the group wasn t enough for allowing, in a more spontaneous way, the negotiation of meanings and the exchange of mathematical ideas. The university-school partnership in decisionmaking was expected by the teachers as a way to validate their teaching practice.